Evaluation of the Accuracy of the Two Kinematic Observing Methods in Global Navigation Satellite Systems Within Forests - داؤد, ِعلي; ندى محفوض; فايز ديب (Latakia University Journal -Engineering Sciences Series, 2024)
In order to manage natural resources and forests and demarcate their boundaries, Global Navigation Satellite Systems (GNSS) contribute to meeting a number of the needs of natural resources specialists, such as forest demarcation, positioning, and mapping, so its accuracy must be assessed. Therefore, the main objective of this research is to evaluate the accuracy of the two Kinematic observing methods in Global Navigation Satellite Systems (GNSS). The first is the Post Processing Kinematic method (PPK), and the second is the method of Real Time Kinematic (RTK), by determining the perimeter and area of the forest, as well as the locations of the surrounding polygon points and the locations of the trees within it, with each of these two methods and comparing the results with the values resulting from observing in the traditional method (Total Station). The results were presented in tables and charts, and indicated that the RTK method of locating polygon points surrounding the forest or its trees has better accuracy than the PPK method, but when calculating the area or perimeter, the accuracy of both methods is similar.